History and the Boundaries of Legality: Historical Evidence at the ECCC - Mamo, Andrew B. (Columbia Journal of Asian Law, 2015)
The Extraordinary Chambers in the Courts of Cambodia (ECCC) began operations in 2006, after a generation of historians and archivists had already collected documents, interviewed victims, perpetrators, and bystanders, and written accounts of the 1970s that directly addressed both the factual questions of what happened in Cambodia and legal questions of individual responsibility. Today, the Documentation Center of Cambodia (DC-Cam) remains the focal point for this historical and archival work. This paper examines the dyadic relationship between the ECCC and DC-Cam and the way that lawyers, scholars, and activists have drawn boundaries between the work of the court and the work of research and scholarship within Cambodian civil society. It argues that, within the prevailing understanding of the relationship between law and society in Cambodian human rights circles, while each element of this dyad needs the other, each must also retain some separation in order to comply with the norms of both fair trial practice and historical scholarship. Two mechanisms make that separation impossible: the use of historians as expert witnesses within the trials; and the debate over reparations as a way to use the trials to contribute to social remembrance of the victims of the Khmer Rouge. Each instance underscores the complex relationship between the ECCC and DC-Cam. The impossibility of this separation need not threaten the court’s legitimacy, as many have argued; instead, it can support a more comprehensive idea of judicial legitimacy.